Reusable fluorescent photocrosslinked polymeric sensor for determining lead ions in aqueous media - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this study, l-vinylimidazole units bearing photocured films were prepared as fluorescent sensors towards Pb2+ in aqueous solutions. The influence of experimental parameters such as pH, time and foreign ion concentrations were investigated. Sensor response was linear over a concentration range of 4.83 x 10(-8) to 4.83 x 10(-7) mol L-1. The sensor was highly sensitive with a detection limit as low as 1.87 x 10(-8) mol L-1, and having a selectivity of over four thousand fold. The response time of the sensor was found to be 5 min. When stored in a desiccator at room temperature the sensor showed good stability after a 5 month period. The fluorescence sensors were successful in the determination of Pb2+ in water samples as well as in the determination of the quantitative amount of lead and the results were satisfying. Compared with previously reported literature, the prepared new sensor is highly sensitive and selective. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Fluorimetric sensor; Photo-curing; Selective lead (II) determination; Vinyl imidazole; MEMBRANE; CHEMOSENSOR